BEST COMMUNITY ENGAGEMENT STRATEGIES TO RAISE CULTURE OF ORGAN DONATION IN PAKISTAN USING THE UNIVERSITY PLATFORM - Erum Zarief Monis; Kinza Waqar (Pakistan Armed Forces Medical Journal, 2020)
Abstract To identify best community engagement strategies, using university platform to raise culture of organ donation in Pakistan. A comprehensive review was done involving extensive literature review and analysis of public opinions. University-level interactions, focus group discussions and debates were also reviewed to identify factors creating hurdles in ethical organ donation. Efforts for organ donation by various sectors including government and nonprofit organizations were made to develop a strategy to improve ethical, medical, legal and religious knowledge on the holistic process of organ donation. Offering financial incentives to suffering families was identified as a source of motivation to encourage organ donations. In this respect, educated and affluent citizens were found most willing. Such eager individuals/groups can be encouraged to pass on training through various community engagement strategies involving multimedia and street-level campaigns. Other effective means of invoking encouragement for organ donation can be through the distribution of inspiring real-life stories. Using the quadruple helix model comprising Academia-Healthcare Industry-Government and Community Partnership, advocacy could be boosted and healthcare services can be improved by making state-of-the-art facilities available for organ perfusion. Public recognition for prominent activists / donors can further advance efforts for the cause.